Assessing the diet of modern and archaeological guanacos from the Great Chaco in Córdoba, Argentina, through stable isotope analysis (δ13C, δ15N) of bone and dentin collagen. Implications for paleoenvironmental and zooarchaeological studies - Weihmüller, María Paula (2024)
The application of stable isotope analyses allows a diachronic characterization of species habitat and feeding behavior, information of utmost importance for zooarchaeological research. In South America, the former distribution of the guanaco (Lama guanicoe) encompassed a much larger territory than the current one. Within the Argentinean Great Chaco, only a small native population persists in Northwestern Córdoba province, Central Argentina, where it was once widely distributed. In this paper, we present the first set of dentin and collagen δ13C and δ15N values for this relict population (N=18) along with archaeological data of guanaco specimens (N=19) dated to the Middle and Late Holocene from the nearby Ongamira valley. Neither deciduous and permanent teeth nor males and females show marked differences within the modern samples. Both modern and archaeological guanaco δ13C values indicate a mixed diet of C3 and, to a lesser extent, C4 plants. Conversely, the δ15N values exhibit distinct signals between the Arid and the Mountain Chaco. The diet breadth of the archaeological guanacos suggests the use of transitional or ecotonal environments, also reflected in the size of their isotopic niche as opposed to modern guanacos. Regarding the timing of the species retraction in the region, there is no evidence of a shift in its habitat during the period between ~4700-1900 14C years BP. We suggest their retraction probably occurred later than previously proposed in regional zooarchaeological models.